Trichloroacetic acid fueled practical amine purifications - Aleena Thomas; Baptiste Gasch; Enzo Olivieri; Adrien Quintard (Beilstein Journal of Organic Chemistry, 2022)
Amine purification have for long been dominated by tedious stepwise processes involving the generation of large amounts of undesired waste. Inspired by recent work on out of equilibrium molecular machinery, using trichloroacetic acid (TCA), we disclose a purification technique considerably decreasing the number of operations and the waste generation required for such purifications. At first, TCA triggers the precipitation of the amines through their protonated salt formation, enabling the separation with the impurities. From these amine salts, simple decarboxylation of TCA liberates volatile CO2 and chloroform affording directly the pure amines. Through this approach, a broad range of diversely substituted amines could be isolated with success.